The ethics of neoaustenism:: from Jane Austen to Taylor Swift in the age of metamodernism - Sánchez Cabrera, Alejandro (International Journal of English Studies, 2025)
This article introduces neoaustenism as a metamodern-feminist sensibility rooted in Jane Austen’s fiction and paradigmatically articulated today through Taylor Swift’s songwriting. While other metamodern-rooted discourses such as neoromanticism revive a largely male genealogy of longing and melancholy, neoaustenism retrieves a specifically feminine grammar of irony, self-reflexivity, and relational ethics. Grounded in affect theory and the ethics of care, the concept reframes vulnerability as a shared resource that turns personal wounds into collective agency. The article first situates neoaustenism within metamodern oscillation and the affective turn. It then traces a gendered genealogy of sentiment from Austen’s heroines to Swift’s layered lyrical voices, showing through close reading how Swift’s songwriting translates Austenian irony and care into pop rituals that foster horizontal communities through reflective nostalgia, audience co-authorship, and embodied practices. Finally, this article argues that neoaustenism holds potential beyond Swift and offers a critical horizon for (re)imagining feminine identity and resilience in neoliberal culture, thus inviting further interdisciplinary inquiry.